Commit f2e1eb75 by Jigyasa Watwani

exact solution diffusion advection moving domain

parent a7a203bf
Showing with 97 additions and 0 deletions
\documentclass[10pt,a4paper]{report}
\usepackage[utf8]{inputenc}
\usepackage{amsmath}
\usepackage{amsfonts}
\usepackage{amssymb}
\usepackage{graphicx}
\usepackage[left=2cm,right=2cm,top=2cm,bottom=2cm]{geometry}
\author{Jigyasa Watwani}
\title{Physics of Growth Regulation in Cells and Tissues - Notes}
\begin{document}
\chapter{Exact solution for advection diffusion equation on a moving domain}
We checked if our numerical solution for the advection-diffusion equation on a moving domain matches the analytical expression in \cite{Simpson2015-xe}
\bibliographystyle{plain}.
The equation we intend to solve is:
\begin{equation} \label{diffusion_advection_equation}
\frac{\partial C}{\partial t} = D\frac{\partial^2 C}{\partial x^2} - \frac{\partial(vC)}{\partial x}
\end{equation}
Here, $C$ is the concentration of the morphogen diffusing and advecting in a $1$-D domain of size $L(t)$.
Let the fixed domain be parameterized by $s$ and the moving domain be parameterized by $x$. We define a map $x(s,t)$. The velocity of a point $s$ at time $t$ is given by
\begin{equation} \label{vel_def}
v=\frac{\partial x(s,t)}{\partial t}
\end{equation}
Eventually, we want to scale $x(t)$ by $L(t)$. So we need to find $L(t)$.
Now,
\begin{equation} \label{length_def}
L(t) = \int_0^{L_0} \frac{\partial x(s,t)}{\partial s} ds
\end{equation}
Let us choose a map $x(s,t) = s \exp(\alpha t) $. The velocity of the domain is then given by (from Eq \ref{vel_def}):
\begin{equation}
v(s,t) = \alpha s \exp(\alpha t)
\end{equation}
or, in the moving domain:
\begin{equation}
v(x,t) = \alpha x
\end{equation}
Thus, for our chosen map, the advection velocity is $v = \alpha x$. We also move the domain by this velocity.
And finally, the length of the domain is given by (from Eq \ref{length_def} and the definition of our chosen map):
\begin{equation}
L(t) = L_0 \exp(\alpha t)
\end{equation}
We now scale variables $x \to \xi = x/L(t)$. Note then that the derivatives transform as:
\begin{equation}
\frac{\partial C}{\partial x} \to \frac{1}{L(t)} \frac{\partial C}{\partial \xi}
\end{equation}
\begin{equation}
\frac{\partial^2 C}{\partial x^2} \to \frac{1}{L(t)^2} \frac{\partial^2 C}{\partial \xi^2}
\end{equation}
and
\begin{equation}
\frac{\partial C}{\partial t} \to \frac{\partial C}{\partial t} - \alpha \xi \frac{\partial C}{\partial \xi}
\end{equation}
Converting Eq(\ref{diffusion_advection_equation}) in terms of $\{\zeta, t\}$
\begin{equation} \label{rescaled1}
\frac{\partial C}{\partial t} = \frac{D}{L(t)^2}\frac{\partial^2 C}{\partial \zeta^2} - \alpha C
\end{equation}
We again scale $t \to T = \int_0^t \frac{D}{L(s)^2}ds $, i.e,
\begin{equation}
T = \frac{D}{2 \alpha L_0^2}(1- \exp(-2 \alpha t))
\end{equation}
or,
\begin{equation}
\exp(-2 \alpha t) = 1-\frac{2 \alpha L_0^2 T}{D} \implies \exp(2 \alpha t) = \frac{D}{D-2\alpha L_0^2 T}
\end{equation}
and again changing variables in Eq(\ref{rescaled1}) from $\{\zeta, t\} \to \{\zeta, T\}$, the derivatives transform as:
\begin{equation}
\frac{\partial C}{\partial t} \to \frac{D-2\alpha L_0^2 T}{L_0^2} \frac{\partial C}{\partial T}
\end{equation}
This implies Eq(\ref{rescaled1}) becomes:
\begin{equation}
\frac{\partial C}{\partial T} + \frac{\alpha C L_0^2}{D - 2 \alpha L_0^2 T}= \frac{\partial^2 C}{\partial \zeta^2}
\end{equation}
This can be solved by separation of variables to give the most general solution:
\begin{equation}
C(\zeta, T) = \exp(-k^2 T) \sqrt{\frac{D - 2\alpha L_0^2 T}{D}}[c_1 \sin(k\zeta) + c_2 \cos(k\zeta)]
\end{equation}
Using Neumann boundary conditions $\partial C/\partial \zeta = 0$ at $\zeta = 0$ and $\zeta = 1$, we get $c_1=0,k=n\pi$.
Thus, for any initial condition, we have,
\begin{equation}
C(\zeta, T) = \sum_n a_n \exp\left(-n^2 \pi^2 T \right) \cos\left(n \pi\zeta\right) \sqrt{\frac{D - 2 \alpha L_0^2 T}{D}}
\end{equation}
This is exactly the same as Eq(11) in the reference with $f(T^\star)=\alpha L_0^2/(2\alpha L_0^2T^\star-D)$. All that is left now is to convert back to the old variables and put in an initial condition:
\begin{equation}
C(x,t) = \sum_n a_n \cos\left(\frac{n \pi x}{L(t)}\right)\exp\left(\frac{-n^2 \pi^2 D(1-\exp(-2\alpha t))}{2 \alpha L_0^2}\right) \exp(-\alpha t)
\end{equation}
This matches the result (13) of the paper.
Putting in the initial condition,
\begin{equation}
C(x,t) = \exp(-\alpha t)\left[1+ 0.2\cos\left(\frac{\pi x}{L_0} \exp(-\alpha t)\right)\exp\left(\frac{-\pi^2D}{2 \alpha L_0^2}(1-\exp(-2 \alpha t))\right)\right]
\end{equation}
\bibliography{ref}
\end{document}
\ No newline at end of file
Markdown is supported
0% or
You are about to add 0 people to the discussion. Proceed with caution.
Finish editing this message first!
Please register or sign in to comment